Activity of a practical psychologist in the education system - Egamberdiev Farkhod Tukhtayevich; Malika Yakubova Sobir janovna (THE INNOVATION ECONOMY, 2026)
this article covers the role, tasks and areas of activity of practical psychologists in the educational sys tem. The importance of such directions as psychological counseling, diagnostics and corrective work is indicated when working with students. Also, in modern education, the role of the psychologist in the comprehensive develop ment of the personality of the student and his cooperation with the pedagogical community were analyzed.